Prevalence of condom use among men who have sex with men and using HIV pre-exposure prophylaxis: Prevalence of condom use in MSM which use PrEP - Oliveira, Wesley; Rodrigues, Enzo Gonsales; Sousa, Artur Penalva de Matos; Lopes, Lucas Casagrande Passoni; Nadai, Mariane Nunes de; Damaso, Ênio Luis (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Sexually transmitted infections (STIs) remain a critical global public health issue. Pre-exposure prophylaxis (PrEP), which involves the daily use of tenofovir and emtricitabine, has proven highly effective in preventing HIV transmission, especially among high-risk groups like men who have sex with men (MSM). However, PrEP usage may unintentionally reduce condom use, potentially increasing the risk of acquiring other STIs. Objective: The aim of this study was to describe the percentage of MSM who use PrEP and use condoms in their sexual activities. Methods: A cross-sectional, with a qualitative and descriptive approach, study was conducted using self-made questionnaires about PrEP usage among MSM. Data collection occurred via social media from October 2021 to May 2022, targeting 154 men aged 18–50 from Bauru, São Paulo, and its surroundings. Results: Of the 154 participants, 86.4% were aware of PrEP, but only 11.03% had ever used it, while 73.37% expressed willingness to use it. Among PrEP users, 5.84% reported contracting an STI during use, with gonorrhea and syphilis being the most common. Condom use was inconsistent across all groups, with only 3.24% of PrEP users and 32.46% of potential users consistently using condoms in all sexual encounters. The findings highlight significant gaps in PrEP usage and condom adherence, emphasizing the need for targeted interventions to address STI prevention and promote consistent condom use. Conclusion: Although PrEP is effective in preventing HIV, this study highlights its association with risky sexual behaviors, leading to higher STI rates. Comprehensive education is essential to mitigate these risks.